The Community Empowerment Based Conservation Program Development Strategy in the Cycloop Mountain Nature Reserve: The Development Strategy of the Community Empowerment Based Conservation Program in the with Fostered Village Models and Conservation Partnerships In the Cycloop Mountains Nature Reserve - Lumban Gaol, Chandra (Indonesian Journal of Social Responsibility Review (IJSRR), 2024)
The community-based conservation program with the Foster Village Model and Conservation Partnership in the Cycloop Mountains Nature Reserve (CAPC) has not gone well, requiring the development of a more effective strategy for its implementation. This paper aims to analyze public perceptions, measure community participation, describe and assess implementation, identify supporting and inhibiting factors, and formulate development strategy directions. This paper was conducted using a qualitative approach with descriptive analysis and SWOT analysis. The results of the writing show that 1) community perceptions of community empowerment programs are in the "good" category, 2) community participation in community empowerment programs is in the "consultation" stage, and 3) implementation of community empowerment programs is generally considered quite good and successful. 4) Factors: factors that support the implementation of community empowerment consist of strengths and opportunities; 5) factors that hinder the implementation of community empowerment consist of weaknesses and threats; 6) the direction of the community empowerment strategy is to increase the capacity of human resources assistants so that assistants are able to build partnerships and more business networks and are able to improve coordination with related agencies.